Ada' Mappurondo Taboo: Ecological Wisdom of the Mamasa Community in Maintaining Natural Preservation - Nurkidam, Andi; Mahyudin (LPPM IAIN Parepare, 2023)
Currently, environmental problems in Indonesia are urgent. For this reason, this requires an ecological wisdom strategy to prevent environmental degradation from getting worse. The aim of this research is to describe a community approach to maintaining the environment which is built on a framework of synergy between local culture and religion through the Pamali Ada' Mappurondo framework. This research used a qualitative approach with a construction phenomenology type. Data was collected through observation, interviews and documentation. This research found that ecological wisdom in the traditional prohibitions of the Mappurondo community has an important role in protecting the ecosystem. In the process, local communities link cosmology and environmental theology when interacting with the natural environment, so that they always avoid things that could damage environmental sustainability. Local customary and religious institutions are used to control ecological change. In this situation, public awareness is created in maintaining and preserving natural environmental balance. This research overview confirms that the role of indigenous communities is needed in efforts to respond to environmental change and damage in Indonesia.